STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM INTEGRASI NILAI MULTIKULTURAL PADA KURIKULUM DAN BUDAYA SEKOLAH DI SMK BHAKTI LOA JANAN - Egiy Dwi Nurristianto; Suratman Suratman; Akhmad Ramli (STKIP Pesisir Selatan, 2026)
This study aims to analyze the principal’s leadership strategies in integrating multicultural values into the curriculum and school culture at SMK Bhakti Loa Janan. The research employs a qualitative case-study approach to gain an in-depth understanding of the phenomenon. Data were collected through observations, interviews, and questionnaires involving the principal, teachers, and students. Data analysis was conducted using an interactive model, including data reduction, data display, and conclusion drawing, supported by source and method triangulation. The results indicate that the principal’s leadership plays a strategic role in integrating multicultural values through school policies, curriculum implementation, and the development of an inclusive school culture. Values such as tolerance, mutual respect, and diversity are internalized not only in the learning process but also in daily social interactions. Questionnaire results also show that students demonstrate a high level of tolerance and can interact harmoniously in a diverse environment. The novelty of this study lies in the integration of principal leadership, curriculum, and school culture in multicultural education, strengthened by data triangulation, contributing to more inclusive and contextual educational practices.